REVIVAL TUJUAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI ERA REVOLUSI INDUSTRI 4.0 - Sadam Fajar Shodiq (AT-TAJDID, 2018)
Designing a learning, an educator is required to be able to formulate learning objectives clearly and firmly, so that the learning process is systematically well organized so that what is contained in the learning objectives can be as expected. The formulation of learning objectives should not be out of the procedure, must be based on graduate competency standards, core competencies, basic competencies and predetermined indicators. There are four procedures in preparing learning objectives, namely (1) audience; (2) behavior; (3) condition; (4) degree.